2020
DOI: 10.1177/2167479520934720
|View full text |Cite
|
Sign up to set email alerts
|

A Summer Country’s Coverage of a Winter Event: Australian Nationalistic Broadcast Focus of the 2018 Winter Olympic Games

Abstract: Broadcast commentary of sport programs often is seen as biased for the “home team.” This study sought to determine differences between how the media framed narratives of Australian and non-Australian Olympians by analyzing prime-time coverage of the 2018 PyeongChang Winter Olympic Games across all of Australia’s Seven Network channels. Because Australia is not a traditional powerhouse at the Winter Games, how the media portrays home team and foreign athletes is of interest in this summer sport country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…While scholars have examined the framing of sporting events by western media predominately from the Global North (Angelini et al, 2017; Liçen & Billings, 2013; Scott et al, 2020), there has been limited research which examines the African perspective from the Global South (Cooky et al, 2013; Nauright & Magdalinski, 2003; Onuwumechili, 2009, 2014; Waliaula, 2012) and no known existing study examining the media framing of an international African professional sports league. Research pertaining to domestic sport leagues with international rosters has covered sports in multiple countries in situations including international competition as well as the effects of roster rules.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…While scholars have examined the framing of sporting events by western media predominately from the Global North (Angelini et al, 2017; Liçen & Billings, 2013; Scott et al, 2020), there has been limited research which examines the African perspective from the Global South (Cooky et al, 2013; Nauright & Magdalinski, 2003; Onuwumechili, 2009, 2014; Waliaula, 2012) and no known existing study examining the media framing of an international African professional sports league. Research pertaining to domestic sport leagues with international rosters has covered sports in multiple countries in situations including international competition as well as the effects of roster rules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous literature has examined how commentators discuss athletes based on the athletes’ nationalities (e.g., Angelini et al, 2017; Billlings & Eastman, 2003; Nauright & Magdalinski, 2003; Scott et al, 2020; Xu & Billings, 2020), gender (e.g., Billings, 2008; Cooky et al, 2013; Eastman & Billings, 2001; Liçen & Billings, 2013) and race (e.g., Bruce, 2004; Eastman & Billings, 2001; Nauright & Magdalinski, 2003; Rada & Wulfemeyer, 2005; Walton & Butryn, 2006). As the BAL consists of athletes from across the African continent, the United States, Europe, Canada, and Australia, there may potentially be national or regional biases (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite Australia’s limited medal success at Rio, viewers might have been primed to think that Australia was more successful than it was, because of the sheer volume of name mentions of their country’s people. However, the results of the 2018 PyeongChang Winter Olympics found that Australians only made up seven of the top-20 most-mentioned athletes; yet, four of the top-10 and the top-2 most-mentioned athletes were from Australia (Scott et al, 2020). While the statistics-driven studies of Australian broadcasters are in their infancy, there are signs that Australian broadcaster of the Olympic Games favor the home nation.…”
Section: The Commonwealth Gamesmentioning
confidence: 99%
“…For national broadcasters, they attempt to use nationalized symbols or languages to emphasize the connection between these athletes, audiences, and the country (Billings et al, 2019). The dichotomy of an “us versus them” narrative has frequently been highlighted in broadcast coverage of major events to encourage viewers to support their nations and their athletes (Scott et al, 2020).…”
mentioning
confidence: 99%